2015
DOI: 10.1002/stem.2248
|View full text |Cite
|
Sign up to set email alerts
|

Murine Mesenchymal Stem Cell Commitment to Differentiation Is Regulated by Mitochondrial Dynamics

Abstract: Mouse skin mesenchymal stem cells (msMSCs) are dermis CD105+CD90+CD73+CD29+CD34− mesodermal precursors which, after in vitro induction, undergo chondro, adipo and osteogenesis. Extensive metabolic reconfiguration has been found to occur during differentiation, and the bioenergetic status of a cell is known to be dependent on the quality and abundance of the mitochondrial population, which may be regulated by fusion and fission. However, little is known regarding the impact of mitochondrial dynamics on the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
185
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(207 citation statements)
references
References 44 publications
14
185
0
1
Order By: Relevance
“…Interestingly, in control condition, increased fission was observed in ASC EMS which may be correlated with apoptosis and decreased proliferation of those cells. Our data stands with a good agreement with Forni et al [47] who observed that mitochondria were more rounded and fragmented during commitment toward chondrogenesis although in murine dermal MSC differentiation. The remodeling of the mitochondrial network is essential for the differentiation program, since these cells' capacity to differentiate when fusion or fission is abrogated.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in control condition, increased fission was observed in ASC EMS which may be correlated with apoptosis and decreased proliferation of those cells. Our data stands with a good agreement with Forni et al [47] who observed that mitochondria were more rounded and fragmented during commitment toward chondrogenesis although in murine dermal MSC differentiation. The remodeling of the mitochondrial network is essential for the differentiation program, since these cells' capacity to differentiate when fusion or fission is abrogated.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, LN vascular endothelial cells expressing MAdCAM-119, and CD105 or CD201 expression by mesenchymal stem or progenitor cells202122 and vascular endothelial cells (Fig. 2), further exemplify the uncertainty surrounding cell lineage determination.…”
Section: Resultsmentioning
confidence: 96%
“…Cell stress can produce cell type specific calcification responses, exemplified by oxidative stress driving SMC but inhibiting osteoblast mineralization 35 . Mfn2 but not Drp1 is elevated during mouse osteoblast differentiation, and Mfn2 knockdown reduces mitochondrial elongation and osteoblast differentiation 52 . Cells from humans that do not express any wild type DRP1 are resistant to H 2 O 2 induced mitochondrial fragmentation 24 .…”
Section: Discussionmentioning
confidence: 94%